REPOSITIONING SERBIA AS A TOURIST DESTINATION - Hamović, Vladana; Cvijanović, Drago; Bošković, Desimir (Economics of Agriculture, 2009)
Tourist activity aligns among the most dynamic and most propulsive economic branches, with multiple effects. It implies tourism's strong movable function in wide spectrum of activities. Among more significant characteristics of modern tourist demand, important for tourism development in rural areas, definitely inserts an observation that the demand enlarges towards non-urban rural and protected natural regions, mountains, spas and villages with more significant healthy-recreational and cultural-historical values. Parallel with that increase requirements for ecological quality and healthy-recreational function of receptive spaces, which must be appropriate for moving, recreation and possibility for applying chosen activities. Therefore, sustainable tourism should make optimal utilization of surrounding natural resources, sustaining important ecological processes and supporting preservation of heritage and biodiversity, while socio-cultural authentication of specific community/household protects their cultural inheritance and traditional values and contributes to understanding and tolerance of other cultures.